Modeling the latent impacts of extreme floods on indoor mold spores in residential buildings: Application of machine learning algorithms - Pakdehi, M.; Ahmadisharaf, E.; Azimi, P.; Yan, Z.; Keshavarz, Z.; Caballero, C.; Allen, J.G. (Environment international, 2025)
•Machine learning (ML) models for quantifying the impacts of flooding on mold spores.•Investigations on two recent hurricanes—Ida and Ian—in the United States.•Key factors for predicting mold were flood depth, bathroom exhaust fan, roof age, air tightness and open window blinds.•Some of the key factors were dependent on the geographic region. Floods can severely impact the economy, environment and society. These impacts can be direct and indirect. Past research has focused more on the former impacts. Of the indirect impacts, those on mold growth in indoor environments that affect human respiratory health (e.g. asthma) have received limited attention. Models can be used to predict these impacts and support development of mitigation and preventive actions. Despite the presence of models for some other impacts of flooding, quantitative models for estimating the impacts of flooding on indoor mold spores are lacking. In this article, we studied the aftermath of two recent hurricanes—Ida and Ian—in the United States and applied machine learning algorithms to develop the first quantitative model for predicting mold spores in buildings. A comprehensive fine-scale database (building level), consisting of flood characteristics, building properties, human indoor activities and existing mold spores, prepared through survey questionnaires, home inspections, laboratory analyses and flood hindcasting, from 60 homes was utilized. The modeling results suggested satisfactory performance for regression-based predictions of indoor mold spores (coefficient of determination or R2 of 0.83 and 0.38). This is the first quantitative model for predicting the impacts of flooding on mold spores. Our study provides a foundation for quantitative assessments of flood impacts on indoor mold spores in residential buildings. This supports insurance companies, public health officials and emergency managers to better assess the impacts of hurricanes and extreme flooding on human respiratory health.